Editorial - Pedro Soares Neves (User Experience & Urban Creativity)
In this issue titled Ubiquity, we explore the omnipresence of concepts, patterns, and phenomena that permeate urban, architectural, and cultural spaces. The term "ubiquity" not only invites us to consider the visible and invisible forces shaping our environment but also challenges us to question how these forces manifest in art, architecture, and society at large. From historical reflections to contemporary debates, the contributions in this issue provide a kaleidoscopic view of the intersections between design, public space, and the socio-political landscapes that frame them.